Analisa Kinerja Mesin Ripple Mill dengan Beban 30 Ton/Jam - Fauzun, Hudri (Lembaga Yasin AlSys, 2024)
The growth of oil palm agricultural land until 2017 was 234 479. Ha, with a production productivity figure of 437 292 tons. (BPS 2017) The development of oil palm plants has been developed in several regions in Indonesia and has become a superior plantation crop. Because it has quite high economic value. One factor that needs to be considered in the company's progress is the issue of smoothness. The production process is greatly influenced by the performance of the machines used. PT. Merbaujaya Indahraya is a subsidiary company of PT. MIG is engaged in processing fresh palm fruit bunches into Crude Palm Oil and Palm Kernel Oil. Fresh fruit bunches are obtained from core gardens and farmers. Core garden with 4 sections of MI Group gardens (MI, Binanga Mandala and Heksa). with a capacity of 30 tons/hour. Processing palm oil into CPO (Crude Palm Oil) has several stations including Loading ramp, Sterilizer, Thresser, Screw Press, clarification, and Kernel. The ripple mill machine is a palm kernel processing machine that is located at the kernel station and is prone to damage, where in the ripple mill machine, the seeds enter between the rotor and the ripple plate being pressed so that they collide with each other and break the shell from the core. So that the core is separated from the shell. This research aims to analyze the performance of the ripple mill machine. From the results of the analysis, an efficiency level of 80% was obtained, with 4 samples taken and varying collection times of around 2 hours within 1 (one) day of production.